Development of Authentic Inquiry Approach Module: A Solution to Improve Senior High School Students' Problem Solving Skills - Mahayani, Luh Riska; Sudiarta, I Gusti Putu; Suharta, I Gusti Putu (Universitas Pendidikan Ganesha, 2025)
The facts in the field show the low problem-solving ability of students. This study aims to develop a learning module with an Authentic Inquiry approach for Mathematics subjects, especially Statistics material for class X of high school to improve students' problem-solving abilities. This study is a design study with the Plomp research procedure, which consists of preliminary research, prototyping, and assessment phases. The subjects in this study were instrument validity experts, teachers who assessed the level of practicality of the module and class X high school students. Data collection instruments included validity and practicality sheets, as well as essay tests (pretest and posttest) to assess module effectiveness. Data were analyzed using paired t-tests and N-gain scores. The results of this study indicate that the tested module meets the criteria for valid, practical and effective, including validity reaching very valid criteria with a score of 3.84 out of a maximum score of 4.00, practicality reaching practical criteria with a score of 4.08 out of a maximum score of 5.00, effectiveness reaching N Gain 0.703 with high effectiveness criteria. The developed module contains inquiry activities that include: Listening to Facts, Formulating Problems and Hypotheses, Designing Solutions, Finding Data, Drawing Conclusions, and Summaries and Self-Evaluations, which are arranged to facilitate understanding of each learning indicator. It can be concluded that, the Development of the Authentic Inquiry Approach Module is effective in improving students' problem-solving abilities. The innovation of the authentic inquiry approach module has implications for improving students' abilities in solving statistical problems.